Neurological manifestations of celiac disease Manifestações neurológicas da doença celíaca - José Ibiapina Siqueira Neto; Ana Carolina Leite Vieira Costa; Francisco George Magalhães; Gisele Sampaio Silva (Arquivos de Neuro-Psiquiatria)
Celiac disease (CD/ Nontropicalsprue, gluten-sensitive enteropathy) is a malabsortive condition in which an allergic reaction to the cereal grain-protein gluten (present in wheat, rye and barley) causes small intestine mucosal injury. The onset is in the first four decades of life, with a female to male ratio of 2:1. It may be associated with a wide spectrum of neurological manifestations including cerebellar ataxia, epileptic seizures, dementia, neuropathy, myopathy and multifocal leucoencephalopathy. We report three patients with neurological manifestations related with CD: one with cerebellar ataxia, one with epilepsy and one with cognitive impairment. The diagnosis of CD was confirmed by serologic tests (antiendomysial and antigliadin antibodies) and biopsy of the small intestine. In two patients the neurological symptoms preceded the gastrointestinal abnormalities and in all of them gluten restriction failed to improve the neurological disability. Conclusion: CD should be ruled out in the differential diagnosis of neurological dysfunction of unknown cause, including ataxia, epilepsy and dementia. A gluten free diet, the mainstay of treatment, failed to improve the neurological disability. A doença celíaca (DC, enteropatia sensível ao glúten) é desordem caracterizada por mal absorção causada por reação alérgica ao glúten, proteína presente em diversos cereais. As manifestações iniciais ocorrem nas primeiras quatro décadas de vida, sendo cerca de duas vezes mais freqüente no sexo feminino. DC pode estar associada a largo espectro de manifestações neurológicas incluindo ataxia cerebelar, epilepsia, demência, neuropatia, miopatia e leucoencefalopatia multifocal. Relatamos três casos de pacientes com manifestações neurológicas da DC: um com ataxia cerebelar, outro com epilepsia e o último com déficit cognitivo. O diagnóstico de DC foi estabelecido com base em testes sorológicos (anticorpos antiendomísio e antigliadina) e biópsia intestinal. Em dois pacientes as alterações neurológicas precederam as gastrointestinais. Em todos os casos a dieta livre de glúten não influenciou o quadro neurológico. Concluímos que o diagnóstico de DC deve ser considerado em pacientes com alterações neurológicas de etiologia indeterminada, incluindo ataxia, epilepsia e demência. Uma dieta sem glúten, a base do tratamento das manifestações gastrointestinais, não foi eficiente em melhorar os sintomas neurológicos em nossos pacientes.